2020
DOI: 10.3389/fbioe.2020.00913
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126 Modulates Palmitate-Induced Migration in HUVECs by Downregulating Myosin Light Chain Kinase via the ERK/MAPK Pathway

Abstract: MicroRNA-126 (miR-126) is an endothelial-specific microRNA that has shown beneficial effects on endothelial dysfunction. However, the underlying molecular mechanism is unclear. The present study evaluated the effects of miR-126 on the cell migration and underlying mechanism in HUVECs treated with palmitate. The present results demonstrated that overexpression of miR-126 was found to decrease cell migration in palmitate-treated HUVECs, with decreased MLCK expression and subsequent decreased phosphorylated MLC l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These findings are in agreement with the literature, where modulation of other miRNAs has been shown to improve palmitate-induced EC dysfunction. 53 For example, overexpression of miR-155 has been shown to inhibit palmitate-induced apoptosis and promote EC proliferation through regulation of the Wnt signaling pathway, 47 whereas miR-126 modulated EC migration through the ERK (extracellular signal-regulated kinase)/MAPK signaling axis in the presence of palmitate 49 ; however, our study is distinct from others. First, we identified DNAJB9, a member of the UPR pathway, to be directly targeted by miR-409-3p to exert its downstream effects on regulation of EC angiogenesis.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…These findings are in agreement with the literature, where modulation of other miRNAs has been shown to improve palmitate-induced EC dysfunction. 53 For example, overexpression of miR-155 has been shown to inhibit palmitate-induced apoptosis and promote EC proliferation through regulation of the Wnt signaling pathway, 47 whereas miR-126 modulated EC migration through the ERK (extracellular signal-regulated kinase)/MAPK signaling axis in the presence of palmitate 49 ; however, our study is distinct from others. First, we identified DNAJB9, a member of the UPR pathway, to be directly targeted by miR-409-3p to exert its downstream effects on regulation of EC angiogenesis.…”
Section: Discussionmentioning
confidence: 52%
“… 43 , 44 Additionally, miRNAs have been implicated in improving various aspects of palmitate-induced EC dysfunction, such as dampening inflammation, apoptosis, and stimulating EC migration. 45 , 46 , 47 , 48 , 49 Here, we used palmitate, a 16-carbon saturated fatty acid and a common circulating saturated FFA, 50 to dissect the role of miR-409-3p and its targets in EC-driven angiogenic responses. Interestingly, while palmitate increased miR-409-3p expression in ECs ( Figure 1 E), neutralization of miR-409-3p expression in ECs in the presence of palmitate significantly increased EC growth and migration ( Figure 2 ), overcoming palmitate-induced EC dysfunction ( Figure S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the contrary, Wang et al demonstrated that miR-126-3p reduced palmitate-induced ERK1/2 phosphorylation in HUVEC. However, miR-126-3p had no effect on ERK1/2 phosphorylation in HUVEC at the basal level [ 33 ]. Those data suggest that miR-126-3p regulates ERK1/2 phosphorylation depending on the specific stimulus with the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among the molecules that EXs carry, miRs show the most important role in regulating cellular function. MicroRNA-126 (miR-126) is an endothelial-specific miR found to be expressed in a broad range of tissues, specifically the vascular system and highly vascularized tissues such as lungs and heart [19]. Like all other miRs, miR-126 also has specific functions in angiogenesis and thus is a prospective target for the regulation of vascular integrity and treating various vascular disorders [20,21].…”
Section: Introductionmentioning
confidence: 99%